Role of clay (Bentonite) on mold making process in foundry metallurgy - Mohd Ichwan, Nasution; Mohd Nasir, Zainal Arif; Che Mohd Ruzaidi, Ghazali; Khairel Rafezi, Ahmad; Faizul, Che Pa; Mohd Fitri, Mohamad Wahid; Murizam, Darus (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.